Interregional Scientific Conference “Readings of Saif Sarai – 2022” (Samara Region, Kamyshla, May 17, 2022) - Giniyatullina L.S. (Золотоордынское обозрение)
On June 15, 2021, within the framework of the Year of Native Languages and National Unity in the Republic of Tatarstan, Marjani Institute of History of the Tatarstan Academy of Sciences hosted the International Scientific Conference “Medieval Written Heritage of the Tatars” (towards the 700th anniversary of the birth of Saif Sarai). The conference was attended by representatives of various scientific centers: Research Center for Islamic History, Art and Culture (IRCICA) at the Organization for Islamic Cooperation, Republican Institute of Higher Education of Belarus, State Historical Museum, Nazarbayev University, University of Wisconsin, Russian Academy of Sciences, G. Ibragimov Institute of Language, Literature and Arts of the Tatarstan Academy of Sciences, Kazan (Volga region) Federal University, and others. The conference covered the following topics: current issues of studying the legacy of Saif Sarai, the reflection of Tatar history in written sources, issues of studying the language of written monuments, literary traditions of medieval Tatars, popularization of the Tatar written heritage, etc. Following the International Scientific Conference, it was decided to continue scientific research and activities related to the work of the medieval Tatar poet Saif Sarai.